El marketing mix como estrategia de posicionamiento para la Cervecería Artesanal Urpi Yuriana E.I.R.L. – Huamachuco - 2017 - Fernández Armas, Roxana de Gracia (2019)
The present research work was prepared with the purpose of analyzing the marketing mix variables and the positioning posed as a problem. What is the relationship between the marketing mix and the positioning for the URPI YURIANA EIRL craft brewery in Huamachuco - 2017? and having as a hypothesis that the marketing mix has a direct relationship in the positioning of the URPI YURIANA E.I.R.L. in Huamachuco, 2017. A field investigation of a correlational descriptive level with two variables was carried out, data collection was done through the quantitative technique of the survey, which was applied to the company's customers. It was concluded that the marketing mix has a direct relationship in the positioning of the URPI YURIANA E.I.R.L. in Huamachuco, 2017 at a level of significance of the “p” value of Chi-square less than 0.05. From the marketing mix used by the Cervecería Artesanal URPI YURIANA E.I.R.L. The following was obtained for its Golden Snake product: The price factor registers a high level, the product factor registers a high level, the square factor a medium level and a low level is registered in the promotion factor. And it is recommended to always strive to make a quality beer, because if you have a great product, customer acquisition costs will decrease and the long-term viability of the brewery will grow, thanks to word of mouth advertising. In addition, as it grows, it is necessary to work with more distributors and develop items for points of sale accompanied by promotions that encourage the greater frequency of consumption of craft beer in customers.